Nowaday current status of bacterial (staphylococcal) carriage and known approaches to overcome it - Isayenko, Olena; Ryzhkova , Taisiia; Kalinichenko , Svitlana; Bilozerskyi , Volodymyr (Annals of Mechnikov’s Institute, 2025)
Currently, determining the current state of bacterial (staphylococcal) carriage, analyzing known approaches to overcoming it, determining a strategy for optimizing the latter and developing new directions for combating bacterial carriage is relevant. The purpose of this work is an informational and analytical review of modern literature on bacterial carriage, including staphylococcal, and methods for combating it. The importance of the human microbiota for its health, the effectiveness of the use of probiotics, prebiotics, synbiotics, metabiotics in dysbiosis to restore the balance of microorganisms are considered. The significant danger of nosocomial infections for the health care system around the world is shown, as well as the particular severity of the course of hospital-acquired infections, which is inherent in weakened people in conditions of armed conflict. It is noted that in emergency situations there is a need to adapt the country’s standard medical care for hospital-acquired infections to modern conditions. The work demonstrates the special place, among nosocomial infections, of staphylococcal infection, in which the most common source of Staphylococcus aureus spread is practically healthy carriers.The importance of monitoring Staphylococcus aureus carriage among different population groups, especially among medical workers, is shown in order to further develop effective strategies for prevention and control of infections. Methods of combating staphylococcal carriage are considered, taking into account the possibility of suspending the initial stage of colonization of the macroorganism by suppressing bacterial adhesion and inhibiting the formation of biofilms of pathogens. The need to develop new approaches to increase the effectiveness of prevention and control of staphylococcal carriage is shown. The information obtained will form the basis for further expansion of current concepts of bacterial carriage, will contribute to the development of a new strategy for the eradication of staphylococci among certain categories of the population, such as medical and pharmaceutical workers, pregnant women, the wounded, etc., which will make it possible to prevent the spread of nosocomial infections of staphylococcal genesis in modern conditions and will contribute to the creation of complex immunobiological preparations of a new generation. The work shows the need to develop new approaches to increase the effectiveness of prevention and control of staphylococcal carriage. The possibility of reducing the persistence of the pathogen on mucous membranes due to blocking adhesive processes by its own surface antigens in combination with stimulation of the local immunity with metabiotics may become an alternative to modern methods of combating nosocomial infections and needs further study.